Structure vulnerability and risk analysis of 4-legged offshore structure - Cheok, J. W.; Kee, T. K.; Chew, L. C.; Saffuan, Wan Ahmad; A., Adnan (Penerbit UMP, 2022)
Offshore structures are commonly used in oil and gas collecting sector. This industry is one of the major economic sector in Malaysia. Since distant earthquakes from neighbour countries (Indonesia and Philippines) had caused significant structural damages in the past few years, the perfomance level of offshore due to seismic effect need to be undergone detailed investigation. Therefore, this research aims to investigate the vulnerability and analyze the risk of 4-legged fixed offshore structure under different excitations. In order to achieve the objectives, SAP 2000 was chosen to analyze the offshore structure modelling by referring to the API (American Petroleum Institute) criteria. Time history, response spectrum and free vibration analysis have been performed. The behaviour of the offshore structure was observed and evaluated through the natural frequencies and periods. Meanwhile, results outcome of the joint displacement, velocity, and acceleration represented the dynamic characteristic of the structure. The 4-legged fixed offshore structure categorized as Immediate Occupancy (IO) based on FEMA 356 guidelines. From the results, it showed that existing 4-legged offshore structures in Malaysia are capable to resist seismic loads and in stable condition.